Prophylactic emicizumab for hemophilia A in the Asia‐Pacific region: A randomized study (HAVEN 5) - Renchi Yang (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background Emicizumab is a subcutaneously administered humanized, bispecific, monoclonal antibody approved for prophylaxis in people with hemophilia A. Methods HAVEN 5 (NCT03315455) is a randomized, open‐label, phase 3 study of individuals aged ≥12 years with severe hemophilia A without factor VIII (FVIII) inhibitors, or hemophilia A of any severity with FVIII inhibitors, across the Asia‐Pacific region. Participants were randomly assigned (2:2:1) to receive emicizumab 1.5 mg/kg once weekly (arm A), emicizumab 6 mg/kg every 4 weeks (arm B), or no prophylaxis (arm C). The primary end point was annualized bleeding rate (ABR) for treated bleeds; ABRs were compared between people receiving emicizumab prophylaxis versus those with no prophylaxis. Secondary end points included ABR for treated target joint bleeds. Safety was also evaluated. Results From April 26, 2018, to January 4, 2019, 70 of 76 screened participants were enrolled and randomized (arm A, n = 29; arm B, n = 27; arm C, n = 14). ABRs (95% confidence interval) for treated bleeds and treated target joint bleeds, respectively, were: arm A, 1.0 (0.53‐1.85) and 0.4 (0.18‐1.09); arm B, 1.0 (0.50‐1.84) and 0.3 (0.12‐0.85); arm C, 27.0 (13.29‐54.91) and 8.6 (3.15‐23.42). The most common adverse event, upper respiratory tract infection, was reported for 14 of 56 (25.0%; emicizumab) and 2 of 14 (14.3%; no prophylaxis) participants. No thrombotic events, thrombotic microangiopathies, or deaths were reported. Conclusion Emicizumab 1.5 mg/kg once weekly and 6 mg/kg every 4 weeks demonstrated bleed control in this study population, was well tolerated, and could improve use of prophylaxis in people with hemophilia A.